2010
DOI: 10.1099/vir.0.019695-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trajectory of the VP1 gene of human enterovirus 71 genogroup B and C viruses

Abstract: From 1963 to 1986, human enterovirus 71 (HEV71) infections in the Netherlands were successively caused by viruses of subgenogroups B0, B1 and B2. A genogroup shift occurred in 1987, after which viruses of subgenogroups C1 and C2 were detected exclusively. This is in line with HEV71 typing in Australia, Europe and the USA, but is distinct from that in the Asian Pacific region, where HEV71 subgenogroups B3–B5 and C4–C5 have caused large outbreaks since 1997. To understand these observations in HEV71 epidemiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
1
57
1
1
Order By: Relevance
“…Phylogenies estimated with the 1D VP1 sequences showed a pattern of continuous lineage turnover for echovirus 30 (enterovirus B species) (17) and enterovirus 71 (enterovirus A species) (18). This indicates that virus variants are continuously emerging and are replacing the earlier prevailing viruses, a pattern similar to that of influenza A virus (19).…”
mentioning
confidence: 76%
“…Phylogenies estimated with the 1D VP1 sequences showed a pattern of continuous lineage turnover for echovirus 30 (enterovirus B species) (17) and enterovirus 71 (enterovirus A species) (18). This indicates that virus variants are continuously emerging and are replacing the earlier prevailing viruses, a pattern similar to that of influenza A virus (19).…”
mentioning
confidence: 76%
“…4). These phylogenetic reconstructions for genogroups B and C additionally place recombination events into the differing evolutionary trajectories of GgB and GgC that have been characterized previously (61,63). GgB is characterized by a series of successive emergence and extinctions of the B1 through B5 subgenogroups over the period from 1970 to the present day, with outbreaks occurring throughout South and East Asia in a cycle of approximately every 3 years (1993, 1997, 2000, 2003, 2006, and 2008) (9,23,46,58,62).…”
Section: Detection Of Recombination In Ev71mentioning
confidence: 87%
“…Screening of large data sets of VP1 sequences provides little if any evidence for any sites in the capsid coding region being subjected to the positive selection that would typically be observed in sites under strong immunological pressure. Consistent with these analyses, there is little evidence from serological cross-neutralization experiments for genogroup-or subgenogroup-specific antibodies, nor indeed the existence of measurable antigenic diversity between EV71 isolates (24,26,28,40,63). However, infections with GgB variants induce higher levels of neutralizing antibodies than GgC, supporting an idea that the emergence of GgC may have been assisted by its intrinsically lower immunogenicity than GgB (40).…”
Section: Detection Of Recombination In Ev71mentioning
confidence: 88%
See 1 more Smart Citation
“…Genotypes B3, B4, B5, C1, C2, C4 and C5 contributed to recent outbreaks [129]. Interestingly, cross-neutralization of different genotypes by immune sera from animals and humans is limited, indicating that EV-A71 became antigenically diverse [130][131][132]. Furthermore, using monoclonal neutralizing antibodies, Chen et al even observed antigenic variation between isolates classified to the same genotype [133].…”
Section: Neutralization Of Picornaviruses Neutralization Of Ev-a71 Anmentioning
confidence: 98%